La comunicación asertiva como herramienta para la satisfacción en la atención a los pacientes que acuden al área de emergencia del Hospital IESS Ibarra - Sinchiguano Morillo, Dayana Lizeth (2024)
The research on assertive communication in the emergency department of the IESS Hospital in Ibarra revealed the importance of adequate and timely patient care. Despite this, deficiencies in communication by healthcare personnel were found, affecting patient satisfaction. The objective of the study was to identify the relationship between assertive communication by healthcare personnel and the level of patient satisfaction. To conduct this research, active listening, empathy, reciprocity in communication, trust, expression of opinions and recommendations, and clarity in expressing symptoms and concerns were analyzed. By addressing these challenges and competencies of healthcare personnel, it is possible to significantly improve the quality of care and patient satisfaction. The study was supported by interviews with healthcare professionals and surveys of patients attending the emergency department to identify perceptions, skills, and needs regarding the quality of communication received from healthcare personnel. Finally, the results obtained led us to identify essential recommendations and practices based on patient satisfaction, which facilitated the implementation of specific actions aimed at improving the quality of communication and care provided in the emergency department.